International Financial Integration through Equity Markets : Which Firms from Which Countries Go Global? - Claessens, Stijn; Schmukler, Sergio L. (World Bank, Washington, DC, 2012)
The authors study international financial integration analyzing firms from various countries raising capital, trading equity, and cross-listing in major world stock markets. Using a large sample of 39,517 firms from 111 countries covering the period 1989-2000, they find that, although international financial integration increases substantially over this period, only relatively few countries and firms actively participate in international markets. Firms more likely to internationalize are from larger and more open economies, with higher income, better macroeconomic policies, and worse institutional environments. These firms tend to be larger, grow faster, and have higher returns and more foreign sales. While changes occur with internationalization, these firm attributes are present before internationalization takes place. The results suggest that international financial integration will likely remain constrained by country and firm characteristics.